Assessing the Influence of Mobile Internet in Aiding Job Seeking for lower-Income Earners in Alexandra, Gauteng - South Africa - Moholi, Bonolo (University of the Witwatersrand, Johannesburg, 2021)
Purpose – The purpose of this study was to establish the extent to which mobile internet can aid job seeking for the lower income employees. The overall goal being to contribute to on-going research on the impact of the internet access to less advantaged communities in order to influence ICT policy makers, recruitment agents and companies to aid job seekers in gaining employment. Methodology approach – This research followed a qualitative approach aided by face-to-face semi-structured interviews with a sample size of 14 actively job-seeking participants in Alexandra, a low LSM township in Johannesburg, South Africa. Findings – This research confirmed that mobile internet can be useful as an aid for job seeking for some lower-Income earners in South Africa. However, there are barriers that impact the full adoption rate and intense online job seeking and these include the high cost of data and devices. Apart from the costs, recruitment agency related issues such lack of trust in the jobs posted, lack of communication with applications, delays in updating online job openings and general negative online experiences when applying for jobs on mobile compared to desktop have also resulted in a slower adoption of exclusive online job seeking. Limitations – The study focused on lower income earners only from Alexandra, South Africa. The economic value derived from owning and using a mobile phone for job seeking was not quantified and further to these participants generally do not know what their exact mobile usage and spend is and therefore ranges were used
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration, Johannesburg 2021
Keywords: Lower income earners; Mobile Internet; Online Job Seeking; UCTD; SDG-8: Decent work and economic growth